Comparing the Efficacy of Radiation Free Machine-Vision Image-Guided Surgery With Traditional 2-Dimensional Fluoroscopy: A Randomized, Single-Center Study. Issue 3 (October 2021) - Dorilio, Jessica; Utah, Nicole; Dowe, Christina; Avrumova, Fedan; Alicea, Daniel; Brecevich, Antonio; Callanan, Tucker; Sama, Andrew; Lebl, Darren R.; Abjornson, Celeste; Cammisa, Frank P.
Background: Three-dimensional (3D) computer-assisted navigation (CAN) has emerged as a potential alternative to 2-dimensional (2D) fluoroscopy in the surgical placement of spinal instrumentation. Recently, 3D-CAN systems have improved significantly in their ability to provide real-time anatomical referencing while shortening the registration and set-up time. A novel system in navigation, Machine-Vision Image-Guided Surgery (MvIGS; 7D Surgical, Toronto, Canada) was cleared by the US Food and Drug Administration, but its potential benefits in reducing intra-operative radiation exposure to patients and enhancing surgical accuracy of pedicle screw placement are not fully known. Purpose : We sought to conduct a prospective, randomized, clinical study comparing the 3D-MvIGS spinal navigation system and 2D-fluoroscopy for pedicle screw insertion up to 3 levels (T10-S1) and for various measures of surgical efficacy. Methods : Sixty-two eligible patients were randomized to receive spine surgery using either the 3D-MvIGS group or the conventional 2D-fluoroscopy for pedicle screw fixation for the treatment of spinal stenosis and degenerative spondylolisthesis. Intra-operative parameters and procedure-related unintended protocol violations were recorded. Results : Operative time and estimated blood loss were not significantly different between groups. Radiation time and exposure to patients were significantly reduced in the 3D-MvIGS group. There was no difference between groups in pedicle screw placement accuracy (2D-fluoroscopy group, 96.6%; 3D-MvIGS group, 94.2%). There were no major complications or cases that required revision surgery. Conclusion : The 3D-MvIGS navigation system performed comparably with 2D-fluoroscopy in terms of pedicle screw placement accuracy and operative time. The 3D-MvIGS showed a significant reduction in radiation exposure to patients. In more complex cases or larger cohorts, the true value of greater anatomical visualization can be elucidated.